If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 47 + -11x = 15 + 5x Solving 47 + -11x = 15 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 47 + -11x + -5x = 15 + 5x + -5x Combine like terms: -11x + -5x = -16x 47 + -16x = 15 + 5x + -5x Combine like terms: 5x + -5x = 0 47 + -16x = 15 + 0 47 + -16x = 15 Add '-47' to each side of the equation. 47 + -47 + -16x = 15 + -47 Combine like terms: 47 + -47 = 0 0 + -16x = 15 + -47 -16x = 15 + -47 Combine like terms: 15 + -47 = -32 -16x = -32 Divide each side by '-16'. x = 2 Simplifying x = 2
| 36-11= | | 1.3t+3(t+8.21)=37.5 | | x^2+11xy+10y^2= | | -7(3+2x)=84 | | 2x+(2x+3)+(2x+4)=2x+2x+(3x+1) | | 35+9104(72)= | | -28x-4=0 | | X(X+1)(X+2)(X+3)=840 | | x^2+7xy+10y^2= | | 190(56)716-= | | X*(X+1)*(X+2)*(X+3)=840 | | p^2-8p-20= | | -44x-728=-772 | | -13-(-7)-2= | | 10a+5x=3b | | 1/2(12x+6)= | | 32-(19)= | | -100=5x | | 3x-(2-7)=133 | | 12+(-11)= | | p^2-21p+20= | | 6-8x=7x-10x-29 | | 3x-2(7)=x | | 4(1+c)=3(c-4) | | .592n+60=5n-12-n | | 8(4c-1)-18=30c+8 | | w^2+19w+18= | | 6(y-2)=4y-22 | | w^2-w-30= | | (6x+3y+1)-(5x+2y-3)= | | w^2+13w-30= | | -16t^2+80t-96=0 |